Causal Relationship between the Stock Market and Exchange Rate in Ukraine - Blahun Ivan I. (Problemi Ekonomiki, 2019)
The aim of the article is to reveal the presence of the impact of changes in the exchange rate on the state of the Ukrainian stock market. As the main identifier of the status of the stock market, there used the index of PFTS as the stock exchange which most actively trades in stocks in Ukraine. The study of the causal relationship between the stock market and the exchange rate is based on the recorded daily data of the PFTS index and the USD / UAN exchange rate for the period 2010–2017. To characterize the time series of the values of the stock market index and exchange rate, their fractal dimensions are used. Assessing the stationarity of the time series of the stock market index and exchange rate with the help of the augmented Dicky–Fuller test and the Phillips–Perron test has allowed to determine that these series are non-stationary. The carried out stationary tests have confirmed the results of causality studies using Granger’s and Johansen’s methodology. It has been established that the inclusion of lagged variables of the stock market PFTS index in the model for describing changes in the exchange rate improves its properties. In the case of the value of the indexes and exchange rate, the tests indicate bilateral causality. In the work, the Sharpe model is used to break down the cumulative exchange rate risk into specific and systematic risks, which conditions the impact of volatility. As a result, it has been found that a one percent increase in the rate of return of the PFTS index causes an average depreciation of the hryvnia to the dollar by 0.03 percentage points. The results obtained are consistent with those calculated for other markets.